Financial Planning at Small Construction Enterprises at the Formation Stage - Verstina, Nataliya Grigorievna; Akimova, Elena Mikhajlovna; Kisel, Tatiana Nikolaevna; Chibisova, Elena Yurievna; Lukinov, Vitaliy Aleksandrovich (International Journal of Economics and Financial Issues, 2015)
Planning is the most important function of management as it is the stage of planning when the main targets of the enterprise are determined and the assessment of the resources necessary for the targets implementation is made. The enterprise within its activities needs different types of resources, however the most important type of resources are financial resources as the availability of other types of resources as well as the opportunity to receive them always depends on the of financial opportunities. Planning of financial resources, determination of their optimum structure, the search of their sources is the most important task of financial management system and financial planning at the enterprise. Financial planning can be carried out with the use of various instruments, the most popular of which is the budgeting system. The advantage of budgeting is the absence of any strict established and fixed rules of planning and accounting as well as the opportunity to regulate forms and to determine indicators for the specific enterprise depending on its requirements. In this article the main features of the construction enterprises which influence the course and features of financial planning are considered. Also the requirements to the budgeting system imposed by the small construction enterprises at a stage of their formation to which, first of all, limitation of funds for planning and conducting the budget accounting belongs are considered in details. The integrated structure of budgets differing in the minimum set of the budget forms is offered as the decision. Some approximate forms of budgets are also developed and presented, however they can be adjusted depending on desire and requirements of the specific enterprise. Keywords: planning, financial planning, business plan, budget, budget management at the enterprise, the project budget, the budget of administrative expenses, the cost budget on salary. JEL Classifications: M21, M41